التأصيل النظري للبحوث السوسيولوجية العربية بين التقليد والبحث عن الهوية - رحـاب, مختار; حمزة بن الطاهر (University of Eloued جامعة الوادي, 2016)
تلجأ العلوم جميعها باختلاف تصنيفاتها إلى اعتماد التراث النظري ذو صلة، كأساس تستند إليه للفهم والتفسير والتحليل، باعتبار النظرية تفيد في تفسير خبرة ما وفهمها على أساس خبرات وأفكار أخرى عامة عن الحياة.ولان النظرية الاجتماعية تحاول أن تكون أشد تنظيماً في نظرها للأفكار والخبرات معا، وتستلهم مقوماتها من الواقع الذي تنشأ فيه، تتجه لتصبح أكثر محلية وأكثر خصوصية لبيئتها، الأمر الذي يفسر صعوبة تطبيقها في بيئة مغايرة لبيئة المنشأ، وفقدان النتائج للصدق والتفسير والفهم الصحيح لها عند اعتمادها . والمهتمون بمجال العلوم الاجتماعية في مجتمعنا العربي ذو الخصوصية ألتاريخه والثقافية المتميزة، انبروا في دفاع مستميت عن النظريات الغربية دون تمحيص أو محاولة لتعريبها، بل أحيانا ما تتعارض هذه النظريات مع قيمه ومقوماته. وتأتي هاته الدراسة لإظهار أهمية النظرية العلمية في الحقل الاجتماعي من جهة وتشخيص الخصوصية العربية في هذا المجال من جهة أخرى ، مع التركيز على المحاولات العربية لخلق براديغما ذات الخصوصية العربية all sciences refuge - depending on their ratings - the adoption of a relevant theoretical heritage, as a basis for understanding, interpretation and analysis, as theory useful in interpreting an experience and understanding based on the experiences of other ideas for public life. Because social theory are trying to be more systematic in its consideration of ideas and experiences together, and inspired its components from the reality in which it is created, it is aiming to become more local and more specific to their environment, which explains the difficulty of their application in different environment to origin environment, and results loss for the sincerity and interpretation correct understanding her when adopted. And involved in the field of social sciences in the Arab society with the privacy of historic and cultural excellence, Strongly defended of Western theories without scrutiny or try to arabization, Even sometimes these theories are incompatible with the values and effervescence. التأصٌل النظري للبحوث السوسٌولوجٌة العربٌة أ.مختار رحـاب / أ. بن الطاهر حمزة 60 )27-95( ص ص This study come to show the importance of scientific theory in the social field on one hand and the diagnosis of the Arab privacy in this area on the other hand, with a focus on Arab attempts to create Pradegma with Arab privacy.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: النظرية الاجتماعية، الاجتماعيون العرب، براديغما; social theory, social Arabs, Pradegma